The effect of omega-3 fatty acid supplementation on weight loss and cognitive function in overweight or obese individuals on weight-loss diet - Salman, Havva Banu; Salman, Mehmet Alper; Akal, Emine Yildiz (Aran Ediciones, S L, 2022)
Objective: omega-3 polyunsaturated fatty acids (PUFAs) are important nutrients that play role in obesity, body lipids, inflammation, and neural function. There is controversy in studies on the effect of omega-3 PUFA supplementation on weight loss and cognitive function. The aim of this study was to investigate the effect of omega-3 PUFA supplementation on weight loss and cognitive function in obese or overweight adults on a weight loss diet. Methods: 40 adult volunteers aged 30-60 years, with body mass index (BMI) between 27.0 and 35.0 kg/m(2), were randomly allocated into two groups. All subjects were involved in a weight loss diet program. The subjects in the omega-3 group (n = 20) also received daily supplementation with 1020 mg of omega-3 PUFAs (580 mg eicosapentaenoic acid (EPA), 390 mg docosahexaenoic acid (DHA), 50 mg other omega-3 PUFAs) for 12 weeks. Anthropometric measurements and body composition analysis were obtained at onset and at weeks 4, 8, and 12 of the study. The Montreal Cognitive Assessment (MoCA) test was used for evaluating cognitive functions at diet onset and at the end of week 12. Results: significant decreases were observed in weight, waist, and BMI in both groups. Abdominal fat mass and percentage decreased more in the omega-3 group than in the control group (p <= 0.05). MoCA scores increased in both groups within time, without statistical significance between groups. Conclusion: omega-3 PUFA supplementation augmented the reduction of abdominal fat mass and percentage in overweight or obese individuals on a weight loss diet. Further studies are required to identify the relationship and mechanisms of action of omega-3 PUFA supplementation on cognitive performance and weight loss.
Keywords: Omega-3; Polyunsaturated tatty acids; Diets; Weight loss; Cognitive functions